Commentary driver training: effects of commentary exposure, practice and production on hazard perception and eye movements - Young, Angela H.; Crundall, David; Chapman, Peter (Elsevier, 2017)
Commentary driving typically involves being trained in how to produce a verbal running commentary about what you can see, what you are doing, what might happen and what action you will take to avoid potential hazards, while driving. Although video-based commentary training has been associated with subsequent hazard perception improvements, it can have a negative impact on hazard perception when a live commentary is produced at test (Young, Chapman, & Crundall, 2014). In the current study we use balanced training and testing blocks to isolate the effects of commentary exposure, production of a commentary with and without practice, and learning from earlier self-generation of commentary on behavioural and eye movement measures. Importantly, both commentary exposed and unexposed groups gave hazard perception responses during the commentary video, ensuring that the unexposed control group remained engaged in the procedure throughout. Results show that producing a live commentary is detrimental to concurrent hazard perception, even after practice, and does not enhance any later effect of commentary exposure. Although commentary exposure led to an initial increase in the accuracy of hazard perception responses, this effect was limited to the first occasion of testing, and showed no later benefits relative to engaged hazard exposure.